Decreased expression of interleukin-37 in the ectopic and eutopic endometria of patients with adenomyosis. (2nd January 2018) - Jiang, Jian Fa; Xiao, Song Shu; Xue, Min
Abstract: Previous studies have shown that alterations of cytokines might play a role in the pathogenesis of adenomyosis. This study aims to investigate the expression of interleukin-37 (IL-37), an anti-inflammatory cytokine, in the eutopic and ectopic endometria of patients with adenomyosis. Endometrial specimens were collected from 30 women with adenomyosis and 20 without adenomyosis. The gene and protein expression of IL-37 was measured using a quantitative real-time polymerase chain reaction and immunohistochemistry, respectively. Compared with the control endometria, the protein expression level and gene level of IL-37 was significantly lower in both the ectopic and eutopic endometria of patients with adenomyosis. The gene and protein expressions of IL-37 in ectopic endometria were lower than those in eutopic endometria of patients with adenomyosis. Our results suggest that there was a low level of IL-37 in the eutopic and ectopic endometria of patients with adenomyosis, and an abnormal inflammatory response might occur in the endometria of patients with adenomyosis.